2017
DOI: 10.7717/peerj.3615
|View full text |Cite
|
Sign up to set email alerts
|

Differences in urinary incontinence symptoms and pelvic floor structure changes during pregnancy between nulliparous and multiparous women

Abstract: BackgroundThis study was performed to compare changes in urinary incontinence (UI) symptoms and pelvic floor structure during pregnancy between nulliparous and multiparous women.MethodsA cross-sectional survey was performed among pregnant women from July 2016 to January 2017. In total, 358 pregnant women from two hospitals underwent an interview and pelvic floor transperineal ultrasound assessment. A questionnaire regarding sociodemographic, gynecological, obstetric features and the International Consultation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 42 publications
1
22
0
1
Order By: Relevance
“…Second, our previous study (21) showed that multiparous women experienced more obvious SUI symptoms and pelvic floor structure changes during pregnancy compared with nulliparous women. First, to better predict SUI during pregnancy, we combined pelvic floor ultrasound parameters and clinical factors.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Second, our previous study (21) showed that multiparous women experienced more obvious SUI symptoms and pelvic floor structure changes during pregnancy compared with nulliparous women. First, to better predict SUI during pregnancy, we combined pelvic floor ultrasound parameters and clinical factors.…”
Section: Discussionmentioning
confidence: 96%
“…First, to better predict SUI during pregnancy, we combined pelvic floor ultrasound parameters and clinical factors. Second, our previous study (21) showed that multiparous women experienced more obvious SUI symptoms and pelvic floor structure changes during pregnancy compared with nulliparous women. However, studies exploring the relation between urinary incontinence during pregnancy and pelvic structure merely took nulliparity into consideration (29,30).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Such contexts have been proven from a study which compared the anatomical changes on the pelvic floor structure between nulliparous and multiparous women. The study reported that the Bladder Neck Decent (BND) was greater in multiparous than nulliparous women suggesting poor urethral support [ 35 ]. Similarly, another study also reported that the rate of UI in nulliparous women (31.8%) was lower than multiparous (47.9%) [ 35 ].…”
Section: Discussionmentioning
confidence: 99%